Property and community - Alexander, Gregory S., 1948-; d (New York ; Oxford : Oxford University Press, 2010)
This work fills a major gap in the legal literature on property and its relationship to community. The essays included differ from past discussions, including those provided by law-and-economics, by providing richer accounts of community.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Right of property -- Philosophy